2020
DOI: 10.20448/2002.83.133.145
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Management Accounting on Decision Making: A Zimbabwean Perspective

Abstract: The aim of the study was to assess the impact of management accounting practices on the decision-making process of the entity operating within the manufacturing sector using a case of Capadvise Foods and Logistics (Pvt) Ltd. The research study was based on the period from 2014 to 2017 which was majorly characterised by huge amounts of losses. Capadvise Foods experienced huge amounts of losses in spite of the existence of management accounting practices. This encouraged the researchers to seek out an in-depth i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Nian and Nair (2017) and Sunarni (2017) disagreed saying management accounting has no effect on decision-making within construction entities as it is undermined by technological advancement, inexperience of accounting staff and intensity of market competition. Nyamwanza et al (2020) found also that management accounting practices were compromised by technological advancement, organizational strategy, organizational factors and intensity of market competition. In addition, Soleimani (2011) states that constant changes in regulations and economic policies play a large role in not using the accounting information system, thus creating insufficient motivation in managers to use accounting information in decision-making.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Nian and Nair (2017) and Sunarni (2017) disagreed saying management accounting has no effect on decision-making within construction entities as it is undermined by technological advancement, inexperience of accounting staff and intensity of market competition. Nyamwanza et al (2020) found also that management accounting practices were compromised by technological advancement, organizational strategy, organizational factors and intensity of market competition. In addition, Soleimani (2011) states that constant changes in regulations and economic policies play a large role in not using the accounting information system, thus creating insufficient motivation in managers to use accounting information in decision-making.…”
Section: Literature Reviewsmentioning
confidence: 99%